Achieving high thermoelectric properties in PEDOT:PSS/SWCNTs composite films by a combination of dimethyl sulfoxide doping and NaBH4 dedoping. (30th August 2022) - Zhang, Li; Xia, Binjie; Shi, Xiao-Lei; Liu, Wei-Di; Yang, Yanling; Hou, Xiaojiang; Ye, Xiaohui; Suo, Guoquan; Chen, Zhi-Gang
Abstract: Incorporating single-walled carbon nanotubes (SWCNTs) can effectively optimize the thermoelectric properties of poly(3, 4-ethylenedioxithiophene):poly(styrenesulfonate) (PEDOT:PSS). However, the thermoelectric performance of flexible PEDOT:PSS/SWCNTs composites is still undesired due to the contradiction between electrical conductivity ( σ ) and Seebeck coefficient ( S ). Here, we adopt dimethyl sulfoxide (DMSO) doping and NaBH4 dedoping to achieve high thermoelectric properties of PEDOT:PSS/SWCNTs composite film by simultaneously improving σ and S . The PEDOT:PSS/SWCNTs composite with 60 wt% SWCNTs exhibits the highest power factor of 411 μW m −1  K −2, originating from high σ of 1718 S cm −1 and high S of 49 μV K −1 . The high σ is derived from the improved carrier transport by insulating PSS removal, the transition of PEDOT chains with ordered stacking structures, and the formed three-dimensional conductive network between PEDOT:PSS and SWCNTs. As well, the decreased carrier concentration induced by the reduction of oxidation level of PEDOT:PSS after NaBH4 dedoping leads to a compromise between σ and S . Besides, a home-made thermoelectric device, fabricated using eight pieces of as-prepared PEDOT:PSS/SWCNTs composite films, shows an output power of 391 nW at a temperature difference of 20 K. Our work indicates that the combination of DMSO doping and NaBH4 dedoping can extend to promote the thermoelectric properties of flexible thermoelectric composite films. Graphical abstract: Image 1 Highlights: Develop combination strategy of DMSO-doping and NaBH4 -dedoping for PEDOT:PSS/SWCNTs. Illustrate an effect of DMSO-doping, SWCNT-incorporating, and NaBH4 -dedoping. Observe highest power factor of 411 μW m −1  K −2 in PEDOT:PSS/SWCNTs composite. Build a thermoelectric device with a high output power of 0.39 μW at a ΔT of 20 K.